Seleção recorrente fenotípica no melhoramento genético de alcachofra e caracterização molecular e química nos distintos ciclos - Costa, Angélica Reolon da (2014)
The artichoke represents a new alternative of profitable crop form small rural property of Rio Grande do Sul, it is a culture of multiple uses, that can be exploited as food, as medicinal, as ornamental and energy source. The objectives these work was: (1) evaluate and select artichoke plants for in natura consumption and establish correlation between main quantitative traits of selective interest; (2) obtain an improved artichoke population for traits of head quality as well as estimate the gains for quantitative traits; (3) evaluate the impact of selection in alleles frequencies of three generation of recurrent selection and estimated the genetic variability by using molecular markers microsatellites (SSRs) and sequence related amplified polymorphism (SRAPs) (4) determine total phenol and antioxidant activity in a population submitted to distinct cycles of phenotypic recurrent selection and verifies modification in these concentrations during the selection processes. To meet these objectives first were evaluated, about 17 quantitative traits and three qualitative, 39 preselected plants from artichoke germplasm collection of University of Passo Fundo, by presenting desired traits for in natura consumption (violet color, circular shape and absence of thorns on the bracts). For obtain an improved artichoke population, was used to phenotypic recurrent selection, where, from a population basis of 147 plants, three cycles of recurrent selection were conducted (C0, C1 e C2). In each cycle was performed the same procedures: evaluation, selection and recombination of selected plants to generate the next generation of recurrent selection, the eventuation the plants in each cycle, was based regarding 12 quantitative and three qualitative traits. The last study constitutes of evaluation of total phenol and antioxidant activity in the artichoke leaves, collected from different plants in each selection cycle (C0, C1 e C2). The study behavior of gene frequencies and genetic variability within each cycle was performed with microsatellite and SRAPs molecular markers. For such was extracted genomic DNA from 30 different plants in each recurrent selection cycle (C0, C1 e C2). The assessments were used 15 microsatellites and seven SRAPs combination, the amplification products was observed in polyacrylamide gels. The extracts were prepared by infusion, and the evaluation of total phenol and reduction power were made immediately after preparation of the extract. Regarding the results in the first study, were significant differences for nine of 17 quantitative traits evaluated and ten of 39 preselected plants and ten evaluated plants, being possible to select ten plants with desirable quantitative traits. The correlation coefficients found can be used as tools for indirect selection for artichoke breeding. The qualitative traits also varied among the plants, being possible to select nine plants with desirable qualitative traits for in natura consumption. The second experiment, the process of phenotypic recurrent selection results in an total increase in the frequency of violet head, head shapes and absence of thorns in the population. There was significant variation among the cycles for most of the quantitative traits. About the final genetic progress, the primary head length and diameter, secondary head number and diameter and bottom thickness showed significant gains. The analysis with molecular markers that were is changes in allele frequencies and there was no reduction of genetic variability in three cycles of recurrent selection. As the chemical analysis, the total phenol content and antioxidant activity resent tendency to reduce during the three cycles. These results indicate the influence of the breeding scheme used on the vegetative parts chemical properties of plants from three phenotypic recurrent selections